Physicochemical properties and antibacterial application of silver nanoparticles stabilized by whey protein isolate. (April 2022) - Zeng, Aoqiong; Wang, Beibei; Zhang, Cheng; Yang, Ruijin; Yu, Shuhuai; Zhao, Wei
Abstract: Nano metal materials have been widely explored to be applied in medical, environmental, and material science. Among these nanoparticles, especially silver nanoparticles (AgNPs), have drawn increasing attention for antimicrobial applications. Most researchers are keen on the development of the biologically friendly capping reagents for the synthesis of AgNPs, instead of unfriendly organic polymers. In this study, the liquid chemical reduction method was used to synthesize AgNPs with edible whey protein isolate (WPI) as a capping reagent. These WPI-AgNPs had a broad size distribution (average diameter of 138.6 nm), and their dimensions could be readily controlled in the range of 22.5–149.6 nm by introducing different concentrations of chloride. Subsequently, it was confirmed that WPI-AgNPs were formed through two mechanisms, which were respectively reduced in situ (without the addition of NaCl) and ex situ (in presence of NaCl) to yield silver nanoparticles. The WPI-AgNPs synthesized in presence of 10 mM of NaCl as mediation reagent were stable at room temperature or 4 °C up to 3 months. Furthermore, the synthesized WPI-AgNPs had a good antibacterial activity toward pathogens including Gram-negative E. coli and Gram-positive S . aureus . The results shed light on method and capping reagent to stabilize silver nanoparticles, which highlighted the potential of WPI and chloride in metal nanoparticle synthesis. Graphical abstract: Scheme of synthesis of AgNPs with WPI as coating reagent. The AgNPs formed by mediation of NaCl showed ideal characteristics and antibacterial effect to pathogens. Image 1 Highlights: AgNPs were synthesized with edible WPI as a stabilizer, forming WPI-AgNPs. The WPI-AgNPs synthesized in the presence of 10 mM of NaCl were rather stable. The WPI-AgNPs have an excellent antimicrobial effect against E. coli and S. aureus.